Species of algae in the river Vorskla what causes «blooming» water - Авраменко, Н. І. (Scientific Progress & Innovations, 2013)
Results of researches of the study of eutrophication processes, in particular the features of dynamics of quantity of different types of algae in the different districts of the Vorskla river are brought. Specific composition of water-plants that results in a «water-bloom» in the river, in Poltava and surrounding villages is described. It is underlined that in most cases the euthrophication of reservoirs is caused by multivariablealgae. Development of almost «clean» monocultures of some species is registered also. The possible biotic and abiotic factors that cause the phenomenon of «flowering» water are examined.